A case of familial central precocious puberty caused by a novel mutation in the makorin RING finger protein 3 gene - Grandone, Anna (BMC Endocr Disord, 2015)
BACKGROUND: Central precocious puberty (CPP) is often familial but its genetic cause is largely unknown. Very recently, the makorin RING finger protein 3 (MKRN3) gene, located on chromosome 15 in the Prader-Willi syndrome (PWS)-associated region (15q11-q13), has been found mutated in 5 families with familial precocious puberty. The MKRN3 is a maternal imprinted gene and the phenotype is expressed only when the MKRN3 mutations are localized on the allele inherited from the father. The function of this gene is not completely known and the phenotype caused by its defect is not yet fully elucidated. We report a new MKRN3 mutation (Pro160Cysfs*14) causing familial CPP. CASE PRESENTATION: The index case is a 7 years old girl showing Tanner stage 3 and pubic hair stage 1. Her bone age evaluated by TW2 method was 10.3 years. Her hormonal data confirmed the diagnosis of central precocious puberty. Familial medical history revealed precocious puberty in a cousin on paternal side. Paternal grandmother had menarche at the age of 9 years and 6 months and premature menopause when she was 36 years old. Genetic analysis revealed a new mutation (c477_485del; Pro160Cysfs*14) in the maternally imprinted MKRN3. Puberty onset was at 5 years in the other affected female family member. Precocious puberty was well controlled by pharmacological therapy. CONCLUSION: We expand the number of the MKRN3 mutations associated with CPP and highlight the importance of an accurate family medical history to disclose the peculiar pattern of inheritance of this gene.